Further Results on Colombeau Product of Distributions - Biljana Jolevska-Tuneska (International Journal of Mathematics and Mathematical Sciences, 2013)
Results on Colombeau product of distributions and are derived. They are obtained in Colombeau differential algebra of generalized functions that contains the space of Schwartz distributions as a subspace and has a notion of “association” that is a faithful generalization of the weak equality in .